French legislation regulating financial administration in colonial Algeria (1839-1898) - mekhalfa, fatmazahra (The Algerian Historical Journal, 2026)
The French colonial administration in Algeria sought to establish a financial system that would achieve the goals of colonialism, represented in the progress of conquest, settlement and revenues, through a legislative vessel that would guarantee the continuation of optimal collection of its revenues from Algerian lands and provide the appropriate climate for the capitalist activity necessary for its existence there. Therefore, this article aims to clarify the most important French financial legislations included in the publications of the French General Government, which are considered the primary source for them, as well as highlighting the financial institutions that were created to manage the French financial system in Algeria.